Comparison of Intraocular Pressure Measurements in Healthy Pediatric Patients using Three Types of Tonometers - Eraslan, Muhsin (Turk J Ophthalmol, 2017)
OBJECTIVES: This study aimed to compare intraocular pressure (IOP) measurements in healthy pediatric patients using three types of tonometers. MATERIALS AND METHODS: Seventy-eight eyes of 78 patients under the age of 18 who underwent a routine ophthalmologic examination were included in the study. IOP was measured using Tono-Pen (TP) tonometry, Goldmann applanation tonometry (GAT), and non-contact tonometry (NCT), consecutively. IOP was adjusted based on central corneal thickness (CCT). Patients with any ocular disorders other than a limited refractive error were excluded from the study. RESULTS: The study consisted of 46 girls and 32 boys. The mean age was 12.6±2.7 (range: 5-17) years. The mean CCT was 559.3±35.3 µm. The mean refractive error was -0.50±1.70. The mean level of visual acuity was 0.98±0.1 (range: 0.3-1.0) using the Snellen chart. Significant differences were found between the measurement results of each of the three tonometric methods. Mean IOP was 12.1±2.2 mmHg for TP, 15.7±2.5 mmHg for GAT, and 17.1±3.1 mmHg for NCT. The correlations between measurement methods revealed that the highest correlation was between NCT and GAT (p<0.001, r=0.670). The second highest correlation was between NCT and TP (p<0.001, r=0.477). The lowest correlation was between GAT and TP (p<0.001, r=0.403). A positive correlation was found between CCT and each IOP measurement method. CONCLUSION: In pediatric patients, TP and NCT measurements were found to be positively correlated with GAT measurements. Because TP measurements were lower than GAT measurements and NCT measurements were higher than GAT measurements, patient follow-ups, treatment strategies, and surgery plans must be organized taking these differences into consideration.